2021
DOI: 10.3390/molecules26071942
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Interactions of Porphyrins with Macromolecules Using NMR Spectroscopy Techniques

Abstract: Porphyrinic compounds are widespread in nature and play key roles in biological processes such as oxygen transport in blood, enzymatic redox reactions or photosynthesis. In addition, both naturally derived as well as synthetic porphyrinic compounds are extensively explored for biomedical and technical applications such as photodynamic therapy (PDT) or photovoltaic systems, respectively. Their unique electronic structures and photophysical properties make this class of compounds so interesting for the multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 239 publications
1
15
0
Order By: Relevance
“…As shown in 1 H NMR spectra (Figures e and S7), the methyl proton peaks of both F127 (∼1.0 ppm) and IMC (∼2.0 ppm) in three IMC@F127 micelles shift the resonance upfield as compared with those of raw F127 (∼1.1 ppm, H d ) or IMC (∼2.1 ppm, H 12 ), and the chemical shift change augments along with the increase of drug loading, given that drug–polymer interaction during the self-assembly of IMC@F127 micelles leads to the shielding of resonance . The splitting of the methyl peak of F127 may result from the J-coupling effect with the adjacent methylene protons or the interaction between IMC and F127. , Figure f shows the thermogravimetric analysis (TGA) curves of IMC, F127, and three IMC@F127 micelles, where the different temperature ranges of 80–100 °C, 250–400 °C, and 350–400 °C correspond to the weight losses of water, , IMC, , and F127, respectively. The weight loss of water in HL micelles is far below the other two counterparts (phase I), implying the sharp decrease of micellar shell hydration with increasing drug loading .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…As shown in 1 H NMR spectra (Figures e and S7), the methyl proton peaks of both F127 (∼1.0 ppm) and IMC (∼2.0 ppm) in three IMC@F127 micelles shift the resonance upfield as compared with those of raw F127 (∼1.1 ppm, H d ) or IMC (∼2.1 ppm, H 12 ), and the chemical shift change augments along with the increase of drug loading, given that drug–polymer interaction during the self-assembly of IMC@F127 micelles leads to the shielding of resonance . The splitting of the methyl peak of F127 may result from the J-coupling effect with the adjacent methylene protons or the interaction between IMC and F127. , Figure f shows the thermogravimetric analysis (TGA) curves of IMC, F127, and three IMC@F127 micelles, where the different temperature ranges of 80–100 °C, 250–400 °C, and 350–400 °C correspond to the weight losses of water, , IMC, , and F127, respectively. The weight loss of water in HL micelles is far below the other two counterparts (phase I), implying the sharp decrease of micellar shell hydration with increasing drug loading .…”
Section: Resultsmentioning
confidence: 91%
“…32 The splitting of the methyl peak of F127 may result from the Jcoupling effect with the adjacent methylene protons or the interaction between IMC and F127. 33,34 Figure 4f shows the thermogravimetric analysis (TGA) curves of IMC, F127, and three IMC@F127 micelles, where the different temperature ranges of 80−100 °C, 250−400 °C, and 350−400 °C correspond to the weight losses of water, 35,36 IMC, 37,38 and F127, 39 respectively. The weight loss of water in HL micelles is far below the other two counterparts (phase I), implying the sharp decrease of micellar shell hydration with increasing drug loading.…”
Section: Resultsmentioning
confidence: 99%
“…Boronated porphyrins and their derivatives can preferentially accumulate in cancer cells with low dark cytotoxicity, 167 , 168 , 169 and thus have potential applications as BNCT/PDT dual sensitizers. 167 , 168 , 169 , 170 The Vicente group reported that boronated chlorin killed T98G cells of human glioma, 171 while Pandey and co-workers found that fluorinated substituents promoted photosensitivity. 172 It was also found that fluorinated porphyrins had higher photokinetic activity than their non-fluorinated counterparts.…”
Section: Applications Of Carboranes As Bnct/photodynamic Therapy Dual Sensitizermentioning
confidence: 99%
“…Porphyrin molecules exhibit molecular flexibility (Cheng et al, 1997) and adopt various conformations (Kingsbury and Senge, 2021). The interactions between the four + N-CH3 groups and the ring current affects the out-of-plane distortion of the compound which results in the protons of the + N-CH3 groups being in different chemical environments, creating the two peaks, δ = 1.08 and δ = 1.20 in the TMPyP (Gjuroski et al, 2021).…”
Section: Molecular Characterizationmentioning
confidence: 99%